La notion d'enrichissement sans cause en droit administratif québécois - Rousseau-Houle, Thérèse (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The problem of unjust enrichment has often been raised in recent years with reference to litigation concerning contracts with public authorities. Many times, parties to such contracts have invoked this principle to obtain compensation for services provided under contracts later declared irregular or void. The courts have then attempted to apply in the context of administrative law the conditions laid down by civil law doctrine for unjust enrichment. The transposition to administrative law of the civil concept of unjust enrichment does not, however, appear to have been adequate. To begin with, the principle of unjust enrichment is difficult to dissociate from the quasi-contract of negotiorum gestio in administrative law. Further, the material and legal conditions of unjust enrichment cannot be applied as a whole to administrative law. In this field, unjust enrichment appears as a true quasi-contract in the sense that it requires the assent of the person enriched. Furthermore, the enrichment must have resulted in a real benefit in the general interest of the administration. These special conditions require a different approach toward the notion of unjust enrichment in administrative law. This approach may be elaborated from the Common Law notion of quantum meruit or from the theory of unjust enrichment in French administrative law. A new concept of unjust enrichment in Quebec administrative law would lead to finding, in the field of quasi-contracts, a solution which would provide for the protection of both public finances and the individual interests of co-contractants.